Axial compression capacity of rectangular CFST columns under random pitting corrosion. (February 2023) - Zhao, Zhongwei; Mo, Shengjie; Gao, Tian
Abstract: To study the effect of random pitting corrosion, this paper presents the change law of the bearing capacity of the rectangular concrete-filled steel tube (CFST) column under the action of axial force with the mass loss ratio of the outer steel tube. Existing experimental data, including the axial ultimate bearing capacity and load displacement curves of the uncorroded and corroded rectangular CFST columns, are collected to verify the rationality of the finite element model. ANSYS software was used to establish a model that can simulate the pitting corrosion, and the results of the finite element analysis were compared with the experiment, which illustrates that the established model can accurately predict the actual load changes. For further research, the corroded thickness tc /t, which include constant tc /t and random tc /t, and other influencing factors such as corrosion pit diameter Dc, steel tube wall thickness t, material strength, shape and section size of specimens are discussed, the results reveal the effect of these parameters on the decline of axial compressive load capacity. Meanwhile, to visually reflect this effect, this study introduces the concept of bearing capacity reduction coefficient Rcs and Rc to express the ratio of bearing capacity of specimens before and after corrosion. The extensive stochastic finite element analysis was carried out, and on this basis, a suitable calculation formula for the reduction factor is proposed to predict the axial compression bearing capacity of the corroded rectangular CFST column by measuring the value of local mass loss ratio of the outer steel.